Disturbance of the muscoloskeletal system in juvenile ankylosing spondylitis and disease developed in the adulthood (involvement of spine and sacroiliac joints). - Ye. D. Yehudina; O. V. Syniachenko; T. R. Polesova; O. E. Chernyshova; M. V. Yermolaeva (Medičnì Perspektivi)
Background. Two forms of ankylosing spondylitis (AS) are distinguished: juvenile and adult, depending on debut age of the disease. The diagnosis of juvenile AS (JAS) is one of the most urgent problems in a pediatric rheumatology. The peculiarities of AS course that onsets in childhood and adulthood are manifested by differences in the nature of a spinal column disturbance. At the same time, the evolution of JAS in adulthood remains unexplored. The goals and objectives of research: to study clinical and X-ray symptoms of spondylopathy and sacroiliitis course, to assess their characteristics in the disease that onset in childhood and adulthood. Material and methods. 217 patients with AS (193 men and 24 women) with an average age of 38 years were examined. The fast-progressing course of the disease was detected in 21% of cases, moderate and high degree of activity – in 79% of cases, the ІІ-ІІІ stage in 82%, and polyarthritis – in 65%. JAS was detected in 16% of cases (all boys), among them the third stage occurred twice more likely than among the other patients. Results. The clinical and radiologic signs of spondylopathy and sacroiliitis are observed in 95% and 97% of the total number of AS cases, respectively, among all patients with JAS lumbago was detected 4,3 times more frequently, sciatic muscles hypotrophy – 7,8 times, "the string symptom" - 2,9 times", the calcification of the spinal cord - 2,3 times, whereas the prevalence of spinal column injury, the severity of cervico-spondylopathy and sacroiliitis among patients with the disease debut in the adulthood is significantly greater, and the involvement in the process of the lumbar and thoracic spine are detected correspondingly twice as often and by 19%, occurrence of dorsalgia is 4 times as often, the limitation of body lateral bendover by 59%, while there are ambiguous dispersion-correlation links with extraarticular (systemic) manifestations of the disease, and the high prevalence of a peripheral articular syndrome regarding spondylopathy in JAS is a negative prognosis sign, and for the remaining patients there are indices of the Lansbury index and the index of arthropathy progression. Conclusion: the onset of AS in adulthood is a risk factor for the severe course of spondylopathy.